Ruští emigranti v německém filmu - Mareš, Petr (Iluminace, 1994)
Review of the study - Alexander Schwarz: Russian emigrants in German film. Case studies on Iosif Ermol'ev and Ivan Mozžuchin.
Keywords: German cinema of the 1920s; Russian emigration; Iosif Ermol'ev; Ivan Mozzhukhin